PENGEMBANGAN SISTEM INFORMASI PRAKTIK KERJA LAPANGAN BERBASIS WEB DI SMK KARTIKA 1-2 PADANG - Aryani Carissa Puteri; Rini Novita; Rahayu Trisetyowati Untari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Field Work Practice (PKL) is one of the important programs in Vocational High Schools (SMK) to equip students with real experience in the industrial world. However, the implementation of PKL at SMK Kartika 1-2 Padang still faces several obstacles, such as manual data management, attendance and activity journals that are prone to manipulation, and the process of collecting reports that is time-consuming and costly. To overcome these problems, this study aims to develop a web-based PKL information system that can facilitate the management of PKL activities effectively and efficiently. This study uses the System Development Life Cycle (SDLC) method with the Waterfall model, which includes the stages of planning, analysis, design, implementation, and system testing. The system design was developed using the Laravel framework with MySQL database support. System testing was carried out in two stages, namely the alpha test which includes Whitebox Testing and Blackbox Testing, and the beta test involving experts and users to assess the quality and level of practicality of the system. The results of the study indicate that the PKL information system that was built has functioned as expected. The alpha test demonstrated that all system components functioned smoothly without significant issues, while the beta test yielded highly satisfactory results, with an average rating of 96.98% from experts and 90.89% from users. Based on these results, this web-based PKL information system is considered highly practical and capable of supporting the management of PKL activities at SMK Kartika 1-2 Padang more effectively, efficiently, and transparently.